2023
DOI: 10.3390/ijms24129846
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Diabetes: The Role of Hypoglycemia

Khaled Hameed Husain,
Saud Faisal Sarhan,
Haya Khaled Ali Abdulla AlKhalifa
et al.

Abstract: Hypoglycemia, a common consequence of diabetes treatment, is associated with severe morbidity and mortality and has become a major barrier to intensifying antidiabetic therapy. Severe hypoglycemia, defined as abnormally low blood glucose requiring the assistance of another person, is associated with seizures and comas, but even mild hypoglycemia can cause troubling symptoms such as anxiety, palpitations, and confusion. Dementia generally refers to the loss of memory, language, problem-solving, and other cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…While HbA1c levels reflect glycemic control over the previous three months, and insulin resistance is a key aspect of T2DM pathophysiology, a more robust marker for long-term glycemic control, such as lifetime cumulative glycemic control levels [ 50 ], might be required to elucidate the exact metabolic mechanisms underlying T2DM-related brain alterations. This suggestion stems from the understanding that the brain’s susceptibility to diabetes-related alterations could result from the cumulative impact of the condition over an extended period, which current HbA1c levels may not adequately represent [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While HbA1c levels reflect glycemic control over the previous three months, and insulin resistance is a key aspect of T2DM pathophysiology, a more robust marker for long-term glycemic control, such as lifetime cumulative glycemic control levels [ 50 ], might be required to elucidate the exact metabolic mechanisms underlying T2DM-related brain alterations. This suggestion stems from the understanding that the brain’s susceptibility to diabetes-related alterations could result from the cumulative impact of the condition over an extended period, which current HbA1c levels may not adequately represent [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and implications underlying cognitive decline, mild cognitive impairment (MCI), and dementia in Type 2 diabetes mellitus (T2DM) have attracted significant attention in recent years since a large number of studies have found that T2DM may increase their incidence rate (Biessels and Despa, 2018;Husain et al, 2023). In this Research Topic, two works addressed interesting aspects of this issue.…”
Section: On the Role Of Type Diabetes Mellitusmentioning
confidence: 99%
“…Since then, the concept that neuroglycopenia in DM subjects-resulting from a hypoglycemic episode-leads to neuronal degeneration with cognitive decline and dementia, has been consolidated. That must be considered not only in insulin-treated T1D, but also in several cases of some drugand insulin-treated T2D (for a review, see [93]).…”
Section: Brief Hystory Of Dm and Cognitive Impairementmentioning
confidence: 99%
“…Since then, DM microvascular disease has contributed to the recognition of DM as a risk factor mainly of VD; however, the mechanisms underlying this association are not completely understood [93]. The homology of cerebral and retinal microvasculature, probably due to their similar embryological origin, provides some insight that, like retinopathy, cerebral small vessel disease (SVD) should also develop in DM (for a review, see [127]).…”
Section: Bbb Dysfunctionmentioning
confidence: 99%